Determining Factors Affecting the Mobilization of Deposits in Egyptian Listed Banks - Abdelzaher, Mai Ahmed (International Journal of Economics and Financial Issues, 2023)
The purpose of this article is to examine the determining variables that, between 2003 and 2019, affected the mobilization of deposits in listed banks in Egypt. The dependent variable for this study is deposit growth, while the independent variables include efficiency ratio, size, inflation rate, market capitalization, loan losses, and loans and receivables. The research was conducted on 12 publicly traded banks. Use of statistical techniques such as descriptive statistics, person correlation matrices, and two-way random effects demonstrated a significant positive correlation between the rate of efficiency ratio, size, inflation rate, market capitalization, net operating cash flow, loan losses, and loans.